Pelaksanaan Tugas Dan Wewenang Dinas Ketenagakerjaan Dan Transmigrasi Kota Medan - Marpaung, Rolando; Marbun, Jaminuddin; Zul, Muaz (ARBITER: Jurnal Ilmiah Magister Hukum, 2020)
Labour inspection is done to monitor compliance with labor legislation that is operationally carried out by labor inspectors from the Department of manpower and transmigration of Medan which is also based on chapter XIV of Law No. 13 Year 2003 on Manpower. This study used qualitative research methods and naturalistic. Based on the results of the study found many workers in the city of Medan who have not received the basic rights in accordance with Law No. 13 Year 2003 on Manpower including non-payment of wages according to the minimum wage, termination of employment (FLE) and payment of overtime pay that does not comply with the provisions by employers. These workers feel their rights are not protected by the government, particularly the Department of Manpower and Transmigration as official employment field.